Socio-economic analysis of ovine livestock farms supported by the young farmer project within the scope of rural development - Muharrem Satar; Engin Sakarya (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out in order to reveal the socio-economic structure and changes in the process of small ruminant enterprises supported by young farmer projects within the scope of rural development in Turkey. Materials and Methods: The materials of the study were composed of data obtained from businesses of small ruminant enterprises first time starting in 2016 thanks to the young farmers project, with a simple random sampling method in Turkey's seven geographical regions selected from 121 enterprises rom provided with face to face interviews. The fate of 40 small ruminants (males + 38 females) given to the enterprises in kind in 2016 within the scope of the project at the end of the control and inspection period of the project, how many of the enterprises have continued their activities after this process; the findings regarding the social and economic status and sustainability of the ongoing enterprises evaluated. Results: It has been determined that the ratio of the enterprises that continue their activities is 85.1%; 87% of the determination of these businesses that continue their activities to continue animal husbandry although approximately one year has passed since the control, inspection and sanction period of the enterprises visited within the scope of the research. It has been determined that the owners of the enterprises composed of young farmers 30 years old on average with low income, 98% are married, 86% are women and more than 90% are secondary school graduated. It has been observed that the spouses and other family members who work as "wage workers in their own business" of the enterprises are also a working collective family business although their profitability is low. Also, it was determined that the public resources used in 2016 in real terms gained a value ratio of 45.3% at the end of 2018 and ratio of 68.7% at the end of 2019. Conclusion: Although it is a positive situation that 85% of the ovine breeding projects implemented in Turkey continue their activities thanks to the young farmer project, İt will contribute to agricultural sustainability if young farmers establish NGOs and/or cooperatives where they can cooperate with themselves and with public institutions/organizations in order to defend their social and economic rights. However, giving the grant not all at once, by dividing it into years and having the applicants prepare a "business plan" will ultimately contribute to the sustainability of the projects, as well as to the youth's staying in the agriculture, livestock sector and their agricultural sustainability.